Tribological properties of winding hoisting rope between two layers with different sliding parameters. (November 2016) - Chang, Xiang-dong; Peng, Yu-xing; Zhu, Zhen-cai; Wang, Da-gang; Gong, Xian-sheng; Zou, Sheng-yong; Sun, Shi-sheng; Xu, Wen-xue
The friction and wear behavior exists in ultra-deep coal mine between multi-layer winding hoisting ropes, and it decreases the rope's service life directly, which threatens the safety coal mine hoist. In order to obtain the tribological properties of winding hoisting rope, the effects of sliding velocity, displacement amplitude, and their combination on the tribological behavior of winding hoisting rope in ultra-deep coal mine were investigated on a self-made test rig. The results show that the effect of velocity on the coefficient of friction and temperature rise is more obvious than the stroke. Additionally, the mean value of the coefficient of friction in steady stage decreases from 0.721 to 0.524 with an increase in velocity and stroke at the same time. Furthermore, the temperature rise increases from about 3.43°C to 13.73°C with the velocity at stable stage, and the stroke has little influence on the temperature rise. Moreover, with the increase in velocity and stroke simultaneously, the damage in the wear region does not become more severe. In addition, the wear mechanisms include abrasive wear and adhesive wear, and its wear characteristics in the wear region are plastic deformation, pits, furrows, broken wires, cracking, and spalling.